Bounty on a baron [large type] - Randisi, Robert J. (Wheeler Publishing large print western, 2010)
No one knows much about the Baron. But one whisper in that cultured accent is enough to set even the most hardened of men shaking in their boots. He's clearly cut from a different cloth than other hired killers in the Wild West, but he's just as deadly. And that's all Decker cares about, because in the eyes of the law, all men are equal, and Decker will make sure the Baron faces American justice.